Analisis Kepemimpinan Adaptif: Solusi UMKM Sup Iga Mas Sugi Menghadapi Tiga Tantangan Utama Bisnis - Jordy Thereanda; Rihva Dwi Andanni; Windy Lestari Br Sihombing; Vivi Nila Sari (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This research analyzes the application of adaptive leadership as a solution for Sup Iga Mas Sugi MSMEs in facing three main business challenges: intense competition, increasing raw material prices, and problems related to business premises. Using a qualitative approach with interview, observation and documentation study methods, this research aims to describe and analyze marketing mix strategies that can be implemented. The research results show that Sup Iga Mas Sugi MSMEs implement various adaptive strategies, including product differentiation through menu innovation, improving service quality, optimizing digital marketing, and developing delivery services. To overcome fluctuations in raw material prices, efficient supply chain management and menu diversification are implemented. The problem of less strategic locations is overcome through increasing online visibility and creating unique experiences for customers. This research concludes that the application of adaptive leadership is effective in overcoming these challenges, provides valuable insight into the application of this theory in the context of MSMEs in Indonesia, and provides practical guidance for MSME actors and policy makers to support the resilience and growth of the MSME sector in Indonesia.